A chromium nitride/carbon nitride containing graphitic carbon nanocapsule hybrid as a Pt-free electrocatalyst for oxygen reduction1. Issue 62 (11th August 2015) - Zhao, Lu; Wang, Lei; Yu, Peng; Zhao, Dongdong; Tian, Chungui; Feng, He; Ma, Jing; Fu, Honggang
<x xml:space="preserve">Abstract</x> A CrN nanoparticle and carbon nitride containing graphitic carbon nanocapsule hybrid has been synthesized, which can be used as a highly-efficient Pt-free electrocatalyst towards oxygen reduction reaction with a dominant 4-electron pathway, superior stability and methanol immunity.